The Effect of Differentiated Learning on Students’ Learning Outcomes in Islamic Religious Education at Senior High Schools - Sania Ivahna Nurmanita; Pahrurroji; Reksiana (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to examine the effect of differentiated instruction on students’ learning outcomes in Islamic Religious Education (IRE), specifically in the cognitive, affective, and psychomotor domains, among tenth-grade students at SMAN 82 Jakarta. The study employed a quantitative associative research design. The population consisted of 92 students, with 90 students selected as the sample using a simple random sampling technique. Data were collected through questionnaires and documentation of students’ IRE achievement scores and analyzed using descriptive statistics and multivariate analysis (MANOVA) with SPSS version 26. The results indicate that differentiated instruction has a statistically significant simultaneous effect on students’ cognitive, affective, and psychomotor learning outcomes. Among these domains, the affective domain showed the strongest effect, suggesting that differentiated learning is particularly effective in enhancing students’ attitudes, motivation, and religious awareness. These findings confirm that differentiated instruction is a relevant and effective pedagogical approach in Islamic Religious Education, especially in supporting the implementation of the Merdeka Curriculum, which emphasizes student-centered, inclusive, and adaptive learning practices.